Enhancement of productivity of manual operation of soya sauce factory - Wahid, Zaharah (2018)
Today, with rapidly changing world and market, SMEs have faced a critical challenge to remain competitive in the business market. Recognizing that sustainability is a key business driver to move forward this study has put practical and fundamental sustainability initiatives needed for improvement in the style of production of a small & medium enterprises( SMEs). In this paper a case study of SME food industry is presented. Work study methodology has been embedded in the strategy which leads to a reduction in production cycle time, non-value adding activities, and production cost. In addition, at the filling and capping line, the layout design of the workplace area was optimized; productivity has been improved and returned on investment (ROI) was within three months